Gynecologic Conditions and Bacterial Vaginosis: Implications for the Non-Pregnant Patient - Richard L. Sweet (Hindawi Limited, 2000)
Bacterial vaginosis is characterized by a shift from the predominant lactobacillus vaginal flora to an overgrowth of anaerobic bacteria. Bacterial vaginosis is associated with an increased risk of gynecologic complications, including pelvic inflammatory disease, postoperative infection, cervicitis, human immunodeficiency virus (HIV), and possibly cervical intraepithelial neoplasia (CIN). The obstetrical risks associated with bacterial vaginosis include premature rupture of membranes, preterm labor and delivery, chorioamnionitis and postpartum endometritis. Despite the health risks associated with bacterial vaginosis and its high prevalence in women of childbearing age, bacterial vaginosis continues to be largely ignored by clinicians, particularly in asymptomatic women. Infect. Dis. Obstet. Gynecol. 8:184-190, 2000.